Reguladores vegetais na germinação, vigor e mobilização de reservas em sementes de Passiflora edulis Sims. F. flavicarpa Degener - Manhone, Pedro Ramon (2014)
The passion fruit seeds have related to their physiological quality problems such as uneven germination, which undermines the vigor and seedling formation. Treatments by soaking the seeds accelerate and standardize germination. The objective of this work